Estudos comparativos da genitália da fêmea no gênero Notholopus Bergroth, 1922 (Hemiptera: Miridae) - Fontes, Argentino Viegas (1978)
Study of the female genitalia of the species of the genus Notholopus Bergroth, intended to verify the value of sclerotized structures for taxonomical purposes. Ten species were studied as follows: N. caboclus (Carvalho e Gomes), N. californicus (Knight), N. carmelitanus Carvalho e Ferreira, N. coreoides Carvalho, N. cuiabanus Carvalho, N. filicornis (Fabricius), N. lunatus (Distant), N. pachycerus (Reuter), N. sertanejus Carvalho, N. sulcaticornis (Stal). Notholopisca previously included by Carvalho as a subgenus of Notholopus is being raised to generic rank. An historical survey concerning female genitalia in the Miridae (Hemiptera), material and methods used,the morphology of abdomen and structures of external and internal genitalia are inclued. Comparative terminology for different areas of abdomen and genital chamber is discussed. The genus Notholopus is characterized, and a list of species included, plus a key for their identification structures of the female genitalia. Description of genital structures and a discussion of sclerites considered of taxonomic value as generic, subgeneric or specific levels is included. An analysis of results, conclusions, bibliography, abreviations used in the text and illustrations are given.